2019
DOI: 10.1002/pat.4652
|View full text |Cite
|
Sign up to set email alerts
|

Design and preparation of poly(lactic acid) hydroxyapatite nanocomposites reinforced with phosphorus‐based organic additive: Thermal, combustion, and mechanical properties studies

Abstract: A new phosphorus-based organic additive (PDA) was designed and successfully synthesized using a three-component reaction for improvement of the thermal and combustion resistance of polylactic acid (PLA). For compensate for mechanical properties of PLA, hydroxyapatite nanoparticles was modified via in situ surface modification with PDA and was used for preparation of PLA nanocomposites. The structure and morphology as well as thermal, combustion, and mechanical properties of the all PLA systems were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Overall, the adding of micro-or nano-fillers to polymers and biopolymers leads to a significant increase of their rigidity, thermal-resistance, stability, barrier properties, and durability [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], although in some cases, the presence of the fillers can induce a reduction of some properties due to the development of inappropriate morphology. Besides, the introduction of naturally occurring fillers (nFil), such as nano-sized layered alumino-silicates (e.g., halloysite, bentonite, beidellite, sepiolite, montmorillonite, etc.…”
Section: Natural Fillers (Nfil)mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the adding of micro-or nano-fillers to polymers and biopolymers leads to a significant increase of their rigidity, thermal-resistance, stability, barrier properties, and durability [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], although in some cases, the presence of the fillers can induce a reduction of some properties due to the development of inappropriate morphology. Besides, the introduction of naturally occurring fillers (nFil), such as nano-sized layered alumino-silicates (e.g., halloysite, bentonite, beidellite, sepiolite, montmorillonite, etc.…”
Section: Natural Fillers (Nfil)mentioning
confidence: 99%
“…Currently published study reports about the improvement of mechanical, thermal, and combustion resistance of polylactic acid (PLA) through adding of hydroxyapatite (HA) nanoparticles, previously modified phosphorus-based organic additive (PDA) [43]. Due to the adding of organomodified HA nanoparticles, the main mechanical properties, such as tensile strength (TS) and Young's modulus (YM), of nanocomposites increase, while, the ductility, i.e., the elongation at break Finally, the authors concluded that the addition of nHA results in significantly less marked decreases in tensile strength and strain to failure as a function of aging time than the unmodified films.…”
Section: Natural Hydroxyapatitementioning
confidence: 99%
“…In recent years, the improvement of flame retardancy without sacrificing the mechanical properties of PLA has been studied extensively by researchers 15,18–23 . Below is a summary of three major ways of enhancing mechanical properties of flame‐retardant PLA: Toughening agentsAdding the toughening agents, such as thermoplastic polyurethane elastomer (TPU), 24 polyethylene glycol (PEG), 25 castable polyurethane elastomer (CPU), 26 PA‐HDA (synthesized from phytic acid and 1,6‐hexanediamine), crosslinking polyurethane (CPU) 27 and plasticizer‐poly(propylene glycol) 28 to improve the mechanical property of PLA are the most common methods.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide (PLA), one of the commercial biodegradable polyesters, exhibits superior mechanical property, biodegradability, and easy processability . It has a variety of potential applications, such as packaging, fishery, electronics, and automobile components . However, the intrinsic poor thermal resistance and high combustibility of PLA restrict its further applications.…”
Section: Introductionmentioning
confidence: 99%